Common variants at 5q33.1 predispose to migraine in African-American children. Issue 12 (28th September 2018) - Chang, Xiao; Pellegrino, Renata; Garifallou, James; March, Michael; Snyder, James; Mentch, Frank; Li, Jin; Hou, Cuiping; Liu, Yichuan; Sleiman, Patrick M A; Hakonarson, Hakon
Abstract : Background: Genome-wide association studies (GWASs) have identified multiple susceptibility loci for migraine in European adults. However, no large-scale genetic studies have been performed in children or African Americans with migraine. Methods: We conducted a GWAS of 380 African-American children and 2129 ancestry-matched controls to identify variants associated with migraine. We then attempted to replicate our primary analysis in an independent cohort of 233 African-American patients and 4038 non-migraine control subjects. Results: The results of this study indicate that common variants at 5q33.1 associated with migraine risk in African-American children (rs72793414, p=1.94×10 −9 ). The association was validated in an independent study (p=3.87×10 −3 ) for an overall meta-analysis p value of 3.81×10 −10 . eQTL (Expression quantitative trait loci) analysis of the Genotype-Tissue Expression data also shows the genotypes of rs72793414 were strongly correlated with the mRNA expression levels of NMUR2 at 5q33.1. NMUR2 encodes a G protein-coupled receptor of neuromedin-U (NMU). NMU, a highly conserved neuropeptide, participates in diverse physiological processes of the central nervous system. Conclusions: This study provides new insights into the genetic basis of childhood migraine and allow for precision therapeutic development strategies targeting migraine patients of African-American ancestry.